The Relationship Between Informed Consent Provision and Anxiety in Patients Undergoing Elective Surgery at RSUD Waled, Cirebon Regency - Ouve Rahadiani Permana; Bambang Wibisono; Meilianda Ezizah (Jurnal EduHealth, 2025)
The incidence of medical errors in Indonesia remains high, one of which is related to the provision of informed consent. Surgical procedures require informed consent, and one effort to reduce patient anxiety is by providing comprehensive information about the surgery through informed consent. Additionally, this process helps patients feel more confident and trusting toward the medical procedures performed by doctors. This study aims to analyze the relationship between informed consent provision and the level of anxiety in patients undergoing elective surgery at RSUD Waled, Cirebon Regency. This research is an analytical observational study with a cross-sectional design. Primary data were collected through questionnaires distributed to elective surgery patients at RSUD Waled, Cirebon Regency. The results showed that 67.1% of patients received complete informed consent, while 32.9% received incomplete informed consent. The levels of patient anxiety were categorized as follows: no anxiety (31.5%), mild anxiety (26.0%), moderate anxiety (9.6%), severe anxiety (8.2%), and very severe anxiety (21.9%). The findings indicate a significant correlation between informed consent provision and the level of anxiety in patients undergoing elective surgery at RSUD Waled, Cirebon Regency.